SCIENCE, VOLCANOES, HURRICANES, AND PREDICTION - Aragón-Vargas, Luis Fernando (2016)
In this editorial, a reflection is presented about some limitations in scientific prediction, using some natural events that happened recently in Costa Rica. It also addresses a few basic concepts in philosophy of science.